Antibacterial Properties of Nutmeg Oil in Pork and Its Possible Mechanism. Issue 3 (16th February 2015) - Cui, Haiying; Zhang, Xuejing; Zhou, Hui; Zhao, Chengting; Xiao, Zhihong; Lin, Lin; Li, Changzhu
Abstract The aim of this study is to investigate the antibacterial characteristics and mechanisms of nutmeg oil. In this paper, 54 chemical compositions of nutmeg oil were analyzed by gas chromatography–mass spectrometry (GC–MS). The major volatile components of nutmeg oil were sabinene (39.12%) and alpha‐pinene (11.96%). In addition, nutmeg oil showed significant antibacterial activity, minimum inhibitory concentration, and minimum bactericide concentration of seven pathogens are 0.05 and 0.1%, respectively, and the nutmeg oil also had a significant effect on inhibiting the growth of Escherichia coli and Staphyloccocus aureus in phosphate buffer saline and pork. Subsequently, in order to reveal the possible antibacterial mechanisms of nutmeg oil against pathogens, the damage of cell membrane was observed by scanning electron microscopy, the loss of 260 nm absorbing material was tested by ultraviolet spectrophotometer, and the cellular adenosine triphosphate concentrations were measured by the Surface Hygiene Test Kit. Finally, the decrease of nucleic acid was evaluated by inverted fluorescence microscope. These results indicated that the antibacterial mechanisms of the nutmeg oil against bacteria might be interpreted as disrupting cell membrane and inhibiting synthesis of DNA. Practical Applications As a natural and safe antibacterial agent, nutmeg oil exhibited good antimicrobial activity against a wide range of spoilage and pathogenic bacteria. Meanwhile, the antimicrobial activity of nutmeg oil has been proved on pork. Based on the results, we believe that nutmeg oil can be applied in meat storage and preservation.